Fusion energy for a sustainable future: a review of capabilities and barriers - Huseynov, Mirtoghrul; Šerevičienė, Vaida (International Conference “Environmental Engineering”, 2026)
Fusion energy has come back into the spotlight, as the demand for electricity is increasing with urbanization, electrification, and new high-energy-intensive industries, but also because fossil fuels are depleted, energy systems also need reliable low-carbon energy. This article considers fusion power as a potentially reliable low-carbon option, using the latest scientific literature and publicly available results from supporting installations, International Thermonuclear Experimental Reactor (ITER), and other international fusion research programs. The study first identifies a high level of aggregation of fusion energy, then summarizes the stated advantages for sustainability and the main obstacles that make it difficult to implement. The analysis shows that the system-wide prospectivity of fusion power is associated with a reliable low-carbon supply, but its near-future commercialization is largely limited by engineering sustainability, resource sustainability, thermal management, and initial cost uncertainty. In conclusion, the article separates the test stages from the requirements of the power plant and concludes that if integrated demonstrations do not quickly eliminate the lack of engineering and costs, fusion power will have more long-term benefits than solutions in the near future.